Efficacy of adjunctive azithromycin versus single-dose cephalosporin prophylaxis for caesarean scar defect: study protocol for a randomised controlled trial. Issue 1 (7th January 2020) - Cai, Yanqing; Pan, Hongjie; Zhang, Jian; Cheng, Weiwei; Shi, Yiru; Zeng, Min; Shi, Liye; Yu, Jin; Shen, Ying; Chen, Shan; Zhu, Qian; Mol, Ben W; et al.
Abstract : Introduction: Perioperative infections may be considered predictors of caesarean scar defect (CSD), and multidose antibiotics have a protective effect against CSD. However, the ability of adjunctive azithromycin combined with cephalosporin to reduce the prevalence of CSD remains unclear. The planned study aims to clarify the protective effect of antibiotics against CSD and to assess the effectiveness of adjunctive azithromycin prophylaxis for CSD. Methods and analysis: This study is a double-blind, parallel-control randomised clinical trial that will be carried out at the International Peace Maternity and Child Health Hospital. A total of 220 eligible patients will be randomised (1:1) to receive either adjunctive azithromycin or single-dose cephalosporin 30 min before the incision. The evaluation criteria are the prevalence and characteristics of CSD as assessed by transvaginal ultrasound (TVU) and saline infusion sonohysterography (SIS) at 42 days, 6 months and 12 months after delivery. The primary outcome will be the prevalence of CSD, and the characteristics of CSD will be assessed by TVU and SIS 42 days after delivery; all other outcomes are secondary. Ethics and dissemination: This protocol received authorisation from the Medical Research Ethics Committee of International Peace Maternity and Child Health Hospital on 25 April 2018 (approval no. GKLW2017-84). The findings will be reported in peer-reviewed publications and presentations at international scientific meetings. Trial registration number: ChiCTR-INR-17013272.